Penerapan Konsep Finite State Automata (FSA) pada Vending Machine Voucher Internet Corner - Ilham Wahyudi Siadi; Kukuh Panggalih; Ahmad Bayhaqqi; Windu Gata (Universitas Indraprasta PGRI Jakarta, 2021)
The Internet today has been widely used by all circles, even young children are familiar with it. However, there are some places that are still not covered by an adequate Internet signal. Therefore, this research makes an effort to create a Vending Machine that can provide a variety of Internet packages that can be used in certainly strategic places. In addition, the machine charges a very affordable price and it is very helpful for Internet users to get proper Internet access in places with very inadequate signal for Internet use. The research applies a Finite State Automata method. After this product is tested using the Finite State Automata method and given to several sources, it receives many quite positive responses, with the expectation it can help the community in enjoying Internet access.